3 HISPANICS WITH THE METABOLIC SYNDROME SHOWED HIGHER INCIDENCE OF ATRIAL FIBRILLATION. (1st March 2006) - Altieri, P. I.; Banchs, H. L.; Crespo, M.; Escobales, N.; Figueroa, Y.; López, J. C.; HernIndez, J.; Mundo, H.; Casillas, P.
Abstract : Atrial fibrillation (AF) is the most frequent arrhythmia after the sixth decade. The incidence in (P) with metabolic syndrome (MS) and diabetes mellitus type II (DM) is not known. A retrospective analysis was undertaken in 173 p. with MS-DM with insignificant coronary disease. The mean age was 60 years. 57% were males and 42.5 females. The mean blood sugar on admission was 169 mg/dL. The mean body mass was 30 kg/m 2 . The ejection fraction was subnormal (52 ± 8%) when compared to our normal group (62 ± 12%), p < .0001. The end-systolic dimension of the left atrium was higher in the MS-DM (46 ± 10 mm) when compared to the normal group (40 ± 8 mm), p < .05. The incidence of (AF) in the MS was 12.9% when compared to the control group (5.9%), p < .001. Causes of this higher incidence are (1) ischemia to the sinus node due to atherosclerosis or vasoconstriction of the sinus node (SN) artery due to an elevated concentration of angiotensin II peripherally, intracoronary, and in the atrial tissue; (2) remodeling of the SN due to left ventricular dysfunction; (3) remodeling of the left and right atrium; (4) hyperinsulinemia influencing the SN through NA+-K+ ATPase; (5) aging; (6) abnormalities of QT dispersion. All of these mechanisms will be discussed.